Sustainable tourism and local productive arrangement: Measuring environmental sustainability on the Discovery Coast - Araújo , Wilson Alves de; Pires, Mônica de Moura (Seven Editora, 2023)
The general objective of this research is to analyze the environmental sustainability of tourism in Bahia, from the perspective of local development. Based on the intense debates about the relationship between development and the environment, this research proposes an interdisciplinary approach based on the environmental problem, specifically regarding the externalities derived from the economic activity exerted by man on the natural environment, especially the tourist activity. This study focuses on the discussion of productive agglomerations as a factor in the development of a locality. In methodological terms, descriptive and methodological research is used, based on bibliographic analysis and field research, with a view to identifying, applying, and evaluating these instruments in the locality of Porto Seguro, Bahia. To this end, the research favors two methodological cuts: a quantitative cut, called Locational Quotient, and an analytical cut, used for the characterization of productive agglomerations in low and medium development regions, called Local Productive Arrangement (LPA). In view of the analyses carried out, it was concluded that the studied locality can be identified as a tourism LPA in the consolidation phase. In the environmental dimension, there was a need to implement public and private actions that direct and enhance measures that increase tourism activity in a sustainable way. It is expected as a result of this work: (i) to improve the understanding of the theoretical and practical aspects of sustainable development; (ii) contribute to the analysis of regional development policies, particularly in the locality studied; and, (iii) subsidize the development of public policies aimed at the sustainable development of tourism. DOI:https://doi.org/10.56238/sevened2023.006-078